Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease. - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

An IFN-STAT Axis Augments Tissue Damage and Inflammation in a Mouse Model of Crohn's Disease - Stolzer, Iris; Dressel, Anja; Neurath, Markus; Günther, Claudia; Chiriac, Mircea-Teodor (Frontiers in Medicine, 2021)
Blocking interferon-function by therapeutic intervention of the JAK-STAT-axis is a novel promising treatment option for inflammatory bowel disease (IBD). Although JAK inhibitors have proven efficacy in patients with active ulcerative colitis (UC), they failed to induce clinical remission in patients with Crohn's disease (CD). This finding strongly implicates a differential contribution of JAK signaling in both entities. Here, we dissected the contribution of different STAT members downstream of JAK to inflammation and barrier dysfunction in a mouse model of Crohn's disease like ileitis and colitis (Casp8ΔIEC mice). Deletion of STAT1 in Casp8ΔIEC mice was associated with reduced cell death and a partial rescue of Paneth cell function in the small intestine. Likewise, organoids derived from the small intestine of these mice were less sensitive to cell death triggered by IBD-key cytokines such as TNFα or IFNs. Further functional in vitro and in vivo analyses revealed the impairment of MLKL-mediated necrosis as a result of deficient STAT1 function, which was in turn associated with improved cell survival. However, a decrease in inflammatory cell death was still associated with mild inflammation in the small intestine. The impact of STAT1 signaling on gastrointestinal inflammation dependent on the localization of inflammation, as STAT1 is essential for intestinal epithelial cell death regulation in the small intestine, whereas it is not the key factor for intestinal epithelial cell death in the context of colitis. Of note, additional deletion of STAT2 was not sufficient to restore Paneth cell function but strongly ameliorated ileitis. In summary, we provide here compelling molecular evidence that STAT1 and STAT2, both contribute to intestinal homeostasis, but have non-redundant functions. Our results further demonstrate that STATs individually affect the distinct pathophysiology of inflammation in the ileum and colon, respectively, which might explain the diverse outcome of JAK inhibitors on inflammatory bowel diseases.
CRIS-Team Scopus Importer:2021-06-25
Keywords: cell death; inflammation; inflammatory bowel disease; Paneth cells; STAT signaling

Effects of glucose concentration in the tumor microenvironment on Non Small Lung Cancer (NSCLC) Progression - Gähler, Alexander; Hohenberger, Katja; Tausche, Patrick; Chiriac, Mircea-Teodor; Rauh, Manfred; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Neurath-Finotto, Susetta (JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Glucose-Restricted Diet Regulates the Tumor Immune Microenvironment and Prevents Tumor Growth in Lung Adenocarcinoma - Gähler, Alexander; Trufa, Denis; Chiriac, Mircea-Teodor; Tausche, Patrick; Hohenberger, Katja; Brunst, Ann-Kathrin; Rauh, Manfred; Geppert, Carol-Immanuel; Rieker, Ralf; Krammer, Susanne; Leberle, Anna; Neurath, Markus; et al. (Frontiers in Oncology, 2022)
BackgroundLung cancer is the second common cancer type in western countries and has a high mortality. During the development and progression of the tumor, the nutrients in its environment play a central role. The tumor cells depend crucially on glucose metabolism and uptake. Tumor cell metabolism is dominated by the Warburg effect, where tumor cells produce large amounts of lactate from pyruvate under aerobic conditions. We thus reasoned that, reducing carbohydrates in the diet might support anti-tumoral effects of current immunotherapy and additionally target tumor immune escape. ObjectivesThe link between reducing carbohydrates to improve current immunotherapy is not clear. We thus aimed at analyzing the effects of different glucose levels on the tumor development, progression and the anti-tumoral immune response. MethodsWe correlated the clinical parameters of our LUAD cohort with different metabolic markers. Additionally, we performed cell culture experiments with A549 tumor cell line under different glucose levels. Lastly, we investigated the effect of low and high carbohydrate diet in an experimental murine model of lung cancer on the tumor progression and different immune subsets. ResultsHere we found a positive correlation between the body mass index (BMI), blood glucose levels, reduced overall survival (OS) and the expression of Insulin-like growth factor-1 receptor (IGF1R) in the lung tumoral region of patients with lung adenocarcinoma (LUAD). Furthermore, increasing extracellular glucose induced IGF1R expression in A549 LUAD cells. Functional studies in a murine model of LUAD demonstrated that, glucose restricted diet resulted in decreased tumor load in vivo. This finding was associated with increased presence of lung infiltrating cytotoxic CD8+ T effector memory (TEM), tissue resident memory T (TRM) and natural killer cells as well as reduced IGFR mRNA expression, suggesting that glucose restriction regulates lung immunity in the tumor microenvironment. ConclusionsThese results indicate that, glucose restricted diet improves lung immune responses of the host and suppresses tumor growth in experimental lung adenocarcinoma. As glucose levels in LUAD patients were negatively correlated to postoperative survival rates, glucose-restricted diet emerges as therapeutic avenue for patients with LUAD.
CRIS-Team WoS Importer:2022-05-27

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

IL-9 Producing Tumor-Infiltrating Lymphocytes and Treg Subsets Drive Immune Escape of Tumor Cells in Non-Small Cell Lung Cancer - Heim, Lisanne; Yang, Zuqin; Tausche, Patrick; Hohenberger, Katja; Chiriac, Mircea-Teodor; Kölle, Julia; Geppert, Carol-Immanuel; Kachler, Katerina; Miksch, Sarah; Graser, Anna; Friedrich, Juliane; Kharwadkar, Rakshin; et al. (Frontiers in Immunology, 2022)
Although lung cancer is the leading cause of cancer deaths worldwide, the mechanisms how lung cancer cells evade the immune system remain incompletely understood. Here, we discovered IL-9-dependent signaling mechanisms that drive immune evasion in non-small cell lung cancer (NSCLC). We found increased IL-9 and IL-21 production by T cells in the tumoral region of the lung of patients with NSCLC, suggesting the presence of Th9 cells in the lung tumor microenvironment. Moreover, we noted IL-9 producing Tregs in NSCLC. IL-9 target cells in NSCLC consisted of IL-9R+ tumor cells and tumor-infiltrating lymphocytes. In two murine experimental models of NSCLC, and in vitro, IL-9 prevented cell death and controlled growth of lung adenocarcinoma cells. Targeted deletion of IL-9 resulted in successful lung tumor rejection in vivo associated with an induction of IL-21 and reduction of Treg cells. Finally, anti-IL-9 antibody immunotherapy resulted in suppression of tumor development even in established experimental NSCLC and was associated with reduced IL-10 production in the lung. In conclusion, our findings indicate that IL-9 drives immune escape of lung tumor cells via effects on tumor cell survival and tumor infiltrating T cells. Thus, strategies blocking IL-9 emerge as a new approach for clinical therapy of lung cancer.
CRIS-Team Scopus Importer:2022-05-20
Keywords: IL-9; immune escape; NSCLC; TIL; tumor immunotherapy

Interferon Lambda Promotes Paneth Cell Death Via STAT1 Signaling in Mice and Is Increased in Inflamed Ileal Tissues of Patients With Crohn's Disease - Günther, Claudia; Ruder, Barbara; Stolzer, Iris; Dorner, Heidrun; He, Gui-Wei; Aden, Konrad; Strigli, Anne; Bittel, Miriam; Zeissig, Sebastian; Rosenstiel, Philip; Atreya, Raja; Neurath, Markus; et al. (Gastroenterology, 2019)
BACKGROUND & AIMS: Interferon lambda (IFNL) is expressed at high levels by intestinal epithelial cells (IECs) and mucosal immune cells in response to infection and inflammation. We investigated whether IFNL might contribute to pathogenesis of Crohn's disease (CD). METHODS: We obtained serum samples and terminal ileum biopsies from 47 patients with CD and 16 healthy individuals (controls). We measured levels of IFNL by enzyme-linked immunosorbent assay and immunohistochemistry and location of expression by confocal microscopy. Activation of IFNL signaling via STAT1 was measured in areas of no, mild, moderate, and severe inflammation and correlated with Paneth cell homeostasis and inflammation. IFNL expression and function were studied in wild-type mice and mice with intestinal epithelial cell-specific (Delta IEC) disruption or full-body disruption of specific genes (Mlkl(-/-), Stat1(Delta IEC), Casp8(Delta IEC), Casp8(Delta IEC)Ripk3(-/-), Casp8(Delta IEC)Tnfr(-/-), Casp8(Delta IEC)Mlkl(-/-), and Nod2(-/-) mice). Some mice were given tail vein injections of a vector encoding a secreted form of IFNL. Intestinal tissues were collected from mice and analyzed by immunohistochemistry and immunoblots. We generated 3-dimensional small intestinal organoids from mice and studied the effects of IFNL and inhibitors of STAT-signaling pathway. RESULTS: Patients with CD had significant increases in serum and ileal levels of IFNL compared with controls. Levels of IFNL were highest in ileum tissues with severe inflammation. High levels of IFNL associated with a reduced number of Paneth cells and increased cell death at the crypt bottom in inflamed ileum samples. Intestinal tissues from the ileum of wild-type mice injected with a vector expressing IFNL had reduced numbers of Paneth cells. IFNL-induced death of Paneth cells in mice did not occur via apoptosis, but required Mixed Lineage Kinase Domain Like (MLKL) and activation of Signal transducer and activator of transcription 1 (STAT1). In organoids, inhibitors of Janus kinase (JAK) signaling via STAT1 (glucocorticoids, tofacitinib, or filgotinib) reduced expression of proteins that mediate cell death and prevented Paneth cell death. CONCLUSIONS: Levels of IFNL are increased in serum and inflamed ileal tissues from patients with CD and associated with a loss of Paneth cells. Expression of a secreted form of IFNL in mice results in loss of Paneth cells from intestinal tissues, via STAT1 and MLKL, controlled by caspase 8. Strategies to reduce IFNL or block its effects might be developed for treatment of patients with CD affecting the terminal ileum.
Keywords: Inflammatory Bowel Diseases; Ileitis; Necroptosis; Cytokine

Regulation and Function of Interferon-Lambda (IFNλ) and Its Receptor in Asthma - Krammer, Susanne; Sicorschi Gutu, Cristina; Grund, Janina; Zirlik, Sabine; Finotto, Susetta; Chiriac, Mircea-Teodor (Frontiers in Immunology, 2021)
Asthma is a chronic respiratory disease affecting people of all ages, especially children, worldwide. Origins of asthma are suggested to be placed in early life with heterogeneous clinical presentation, severity and pathophysiology. Exacerbations of asthma disease can be triggered by many factors, including viral respiratory tract infections. Rhinovirus (RV) induced respiratory infections are the predominant cause of the common cold and also play a crucial role in asthma development and exacerbations. Rhinovirus mainly replicates in epithelial cells lining the upper and lower respiratory tract. Type III interferons, also known as interferon-lambda (IFNλ), are potent immune mediators of resolution of infectious diseases but they are known to be involved in autoimmune diseases as well. The protective role of type III IFNs in antiviral, antibacterial, antifungal and antiprotozoal functions is of major importance for our innate immune system. The IFNλ receptor (IFNλR) is expressed in selected types of cells like epithelial cells, thus orchestrating a specific immune response at the site of viruses and bacteria entry into the body. In asthma, IFNλ restricts the development of TH2 cells, which are induced in the airways of asthmatic patients. Several studies described type III IFNs as the predominant type of interferon increased after infection caused by respiratory viruses. It efficiently reduces viral replication, viral spread into the lungs and viral transmission from infected to naive individuals. Several reports showed that bronchial epithelial cells from asthmatic subjects have a deficient response of type III interferon after RV infection ex vivo. Toll like Receptors (TLRs) recognize pathogen-associated molecular patterns (PAMPs) expressed on infectious agents, and induce the development of antiviral and antibacterial immunity. We recently discovered that activation of TLR7/8 resulted in enhanced IFNλ receptor mRNA expression in PBMCs of healthy and asthmatic children, opening new therapeutic frontiers for rhinovirus-induced asthma. This article reviews the recent advances of the literature on the regulated expression of type III Interferons and their receptor in association with rhinovirus infection in asthmatic subjects.
CRIS-Team Scopus Importer:2021-12-10
Keywords: asthma; epithelial cells; exacerbation; interferon; rhinovirus; TLR7/8

Severe Acute Respiratory Syndrome Coronavirus 2 Attachment Receptor Angiotensin-Converting Enzyme 2 Is Decreased in Crohn's Disease and Regulated By Microbial and Inflammatory Signaling - Patankar, Jay Vasant; Lehmann, Malte; Kühl, Anja A.; Atreya, Raja; Becker, Christoph; Gonzalez-Acera, Miguel; Schmitt, Heike; Gamez-Belmonte, Reyes; Mahapatro, Mousumi; Diemand, Leonard; Hartmann, Leonie; Mascia, Fabrizio; et al. (Gastroenterology, 2021)
CRIS-Team Scopus Importer:2021-02-12

STAT1 deficiency supports PD-1/PD-L1 signaling resulting in dysfunctional TNFα mediated immune responses in a model of NSCLC - Friedrich, Juliane; Heim, Lisanne; Trufa, Denis; Sirbu, Horia; Rieker, Ralf; Neurath-Finotto, Susetta; Chiriac, Mircea-Teodor (Oncotarget, 2018)
In this study we described that Signal Transducer and Activator of Transcription 1 (STAT1) is a key point regulator of PD-1 in tumour infiltrating lymphocytes and PD-L1 in Tumour associated macrophages (TAM) in NSCLC. In our murine model of adenocarcinoma targeted deletion of Stat1 was found associated with enhanced tumour growth, impaired differentiation into M1-like macrophages from the bone marrow, the accumulation of tumor associated macrophages overexpressing PD-L1 and impaired T cell responses in the tumor microenvironment by affecting TNFα responses. In our human NSCLC patient cohort we found that loss of isoforms STAT1 α and STAT1β mRNA in the tumoural region of the lung correlates with increased tumor size in NSCLC patients. Therefore, STAT1 isoform regulation could be considered for future therapeutical strategies associated to current immune-checkpoint blockade therapy in NSCLC.
EVALuna2:207415

STAT2 Controls Colorectal Tumorigenesis and Resistance to Anti-Cancer Drugs - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Becker, Christoph; Neurath, Markus (Cancers, 2023)
Colorectal cancer (CRC) is a significant socioeconomic burden in modern society and is accountable for millions of premature deaths each year. The role of signal transducer and activator of transcription 2 (STAT2)-dependent signaling in this context is not yet fully understood, and no therapies targeting this pathway are currently being pursued. We investigated the role of STAT2 in CRC using experimental mouse models coupled with RNA-sequencing (RNA-Seq) data and functional assays with anti-cancer agents in three-dimensional tumoroids. Stat2−/− mice showed greater resistance to the development of CRC in both inflammation-driven and inflammation-independent experimental CRC models. In ex vivo studies, tumoroids derived from Stat2−/− mice with the multiple intestinal neoplasia (Min) mutant allele of the adenomatous polyposis coli (Apc) locus exhibited delayed growth, were overall smaller and more differentiated as compared with tumoroids from ApcMin/+ wildtype (WT) mice. Notably, tumoroids from ApcMin/+ Stat2−/− mice were more susceptible to anti-cancer agents inducing cell death by different mechanisms. Our findings clearly indicated that STAT2 promotes CRC and suggested that interventions targeting STAT2-dependent signals might become an attractive therapeutic option for patients with CRC.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anti-cancer therapy; Apc; colorectal cancer mouse model; STAT2; tumoroid

The role of interferon type I and type III receptors in rhinovirus induced allergic asthma - Krug, J.; Kölle, Julia; Kiefer, Alexander; Vuorinen, T.; Xepapadaki, P.; Stanic, B.; Akdis, M.; Zimmermann, Theodor; Papadopoulos, N. G.; Finotto, Susetta; Chiriac, Mircea-Teodor (ALLERGY, 2020)
CRIS-Team WoS Importer:2020-10-02

TLR7/8 regulates type I and type III interferon signalling in rhinovirus 1b-induced allergic asthma - Krug, Jasmin; Kiefer, Alexander; Kölle, Julia; Vuorinen, Tytti; Xepapadaki, Paraskevi; Stanic, Barbara; Chiriac, Mircea-Teodor; Akdis, Muebeccel; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Finotto, Susetta (European Respiratory Journal, 2021)
Introduction: Interferon (IFN) responses have been reported to be defective in rhinovirus (RV)-induced asthma. The heterodimeric receptor of type I IFN (IFN-α/β) is composed of IFN-αR1 and IFN-αR2. Ligand binding to the IFN-α/β receptor complex activates signal transducer and activator of transcription (STAT) proteins STAT1 and STAT2 intracellularly. Although type III IFN (IFN-λ) binds to a different receptor containing IFN-λR1 and interleukin-10R2, its triggering leads to activation of the same downstream transcription factors. Here, we analysed the effects of RV on IFN type I and III receptors, and asked about possible Toll-like receptor 7/8 (TLR7/8) agonist R848-mediated IFN-αR1 and IFN-λR1 regulation. Methods: We measured IFN-α, IFN-β and IFN-λ and their receptor levels in peripheral blood mononuclear cell (PBMC) supernatants and cell pellets stimulated with RV1b and R848 in two cohorts of children with and without asthma recruited at pre-school age (PreDicta) and at primary school age (AGENDAS) as well as in cell supernatants from total lung cells isolated from mice. Results: We observed that R848 induced IFN-λR mRNA expression in PBMCs of healthy and asthmatic children, but suppressed IFN-αR mRNA levels. In murine lung cells, RV1b alone and together with R848 suppressed IFN-αR protein in T-cells compared with controls and in total lung IFN-λR mRNA compared with RV1b infection alone. Conclusions: In PBMCs from pre-school age children, IFN-αR mRNA was reduced and IFN-λR1 mRNA was induced upon treatment with the TLR7/8 agonist R848, thus suggesting new avenues for induction of antiviral immune responses in paediatric asthma.
CRIS-Team Scopus Importer:2021-06-04